2017
DOI: 10.1002/ijc.31139
|View full text |Cite
|
Sign up to set email alerts
|

Does HPV status influence survival after vulvar cancer?

Abstract: High-risk human papillomavirus (HPV) infection is essential in the carcinogenesis of a substantial part of anogenital and oropharyngeal cancers and has additionally been shown to be a possible predictive marker for survival, especially in oropharyngeal cancer. Studies examining the influence of HPV status on survival after vulvar cancer have been conflicting and limited by small study populations. Therefore, the aim of this review and meta-analysis was to examine whether HPV status influences survival after vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 53 publications
(196 reference statements)
2
34
0
4
Order By: Relevance
“…Our results support the hypothesis that HPV-positive and HPVnegative penile cancers differ in relation to survival outcome, which has also been found in other HPV-associated cancers including vulvar and oropharyngeal SCC (12,15). However, the explanation for the prognostic significance of HPV status is still unclear.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results support the hypothesis that HPV-positive and HPVnegative penile cancers differ in relation to survival outcome, which has also been found in other HPV-associated cancers including vulvar and oropharyngeal SCC (12,15). However, the explanation for the prognostic significance of HPV status is still unclear.…”
Section: Discussionsupporting
confidence: 86%
“…HPV status has been identified as a possible prognostic marker in some HPV-associated cancers; specifically, HPV-positive oropharyngeal squamous cell carcinomas (SCC) have a more favorable clinical outcome compared with HPV-negative (8)(9)(10)(11). In addition, in a recent meta-analysis we found that women with HPV-positive vulvar cancer have a superior overall survival (OS) and disease-free survival (DFS) compared with women with HPV-negative vulvar cancer (12). Penile cancer displays many similarities to vulvar cancer including histology, risk factors, and natural history (13); however, studies examining the association between HPV status and survival in penile cancer are often inconclusive because of small study populations.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach was previously con rmed by Sandberg et al [22] while detecting protein alterations related to HPV infection in a set of VSCC tumors. An increasing evidence suggests that HPVharboring VSCC tumors are less aggressive, though some ambiguities remain regarding the prognostic value of HPV status because of the different HPV testing methods applied, and the low numbers of cases examined in some studies [23][24][25]. In our study, we analyzed a cohort of early-stage VSCC patients with a long-term follow-up after surgery, which enabled strati cation of cases according to treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible to fully assess HPV positivity, nor the true rate of VaIN recurrence in this cohort, but two interesting findings in the literature regarding HPV and VaIN recurrence are worth noting here. First, while HPV positivity is a known precursor to anogenital dysplasia and cancer, a recent meta-analysis demonstrated that HPV positivity in vulvar cancer and other cancers, head and neck cancer, for example, predicted significantly longer survival [25]. Second, studies that reported on factors associated with VaIN and its recurrence posttreatment suggested that among the general, non-HIV population the correlation may be due to closer monitoring that occurs after hysterectomy [15].…”
Section: Discussionmentioning
confidence: 99%